2014
DOI: 10.1128/mcb.00103-14
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Failure Promotes Positioning of Lysosomes around the Aggresome via Local Block of Microtubule-Dependent Transport

Abstract: bUbiquitinated proteins aggregate upon proteasome failure, and the aggregates are transported to the aggresome. In aggresomes, protein aggregates are actively degraded by the autophagy-lysosome pathway, but why targeting the aggresome promotes degradation of aggregated species is currently unknown. Here we report that the important factor in this process is clustering of lysosomes around the aggresome via a novel mechanism. Proteasome inhibition causes formation of a zone around the centrosome where microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 44 publications
6
55
0
Order By: Relevance
“…Additionally, we demonstrate that the JUNQ is asymmetrically inherited, providing a basis for further study of how damaged cellular material is partitioned during division. Direct observation of misfolded protein turnover in IBs reinforces the predictions of many studies (15,29) suggesting that inclusions are not passive by-products of protein aggregation, but rather serve an important quality-control function in the cell. Seeing JUNQ formation and maturation as a dynamic process helps to reconcile divergent observation into a coherent model.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, we demonstrate that the JUNQ is asymmetrically inherited, providing a basis for further study of how damaged cellular material is partitioned during division. Direct observation of misfolded protein turnover in IBs reinforces the predictions of many studies (15,29) suggesting that inclusions are not passive by-products of protein aggregation, but rather serve an important quality-control function in the cell. Seeing JUNQ formation and maturation as a dynamic process helps to reconcile divergent observation into a coherent model.…”
Section: Discussionsupporting
confidence: 78%
“…Although IBs were suspected of mediating misfolded protein degradation due to association with ubiquitin, proteasomes, and lysosomes (21,29), little direct evidence existed for degradation within the IB, as opposed to clearance from the IB by diffusion followed by degradation elsewhere. Our 3D longitudinal experiments demonstrate protein turnover in the JUNQ.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the synergistic control of Dronc protein levels by the UPS and autophagy, we considered that, because the UPS and autophagy are mechanistically linked, impairment of the UPS can enhance autophagy, which is often referred to as compensatory autophagy 1,[19][20][21][22][23][24][25][26][27] (reviewed by Park and Cuervo, 3 Wojcik 28 and Lamark and Johansen 29 ). For example, in Drosophila, compensatory autophagy after proteasome impairment has been reported in neurons, in fat body cells and in adult flies.…”
Section: Simultaneous Inactivation Of Both the Proteasome And Autophamentioning
confidence: 99%
“…16 The incorporation of Atg8 fusion proteins (for example, with green fluorescent protein (GFP) and/or mCherry) into autophagosomes is often used as a marker for autophagosomes 17 and autophagic flux. 18 Although it was initially assumed that the UPS and autophagy are independent of each other, recent evidence has suggested that there is crosstalk and feedback between the two 1,[19][20][21][22][23][24][25][26][27] (reviewed by Park and Cuervo, 3 Wojcik 28 and Lamark and Johansen 29 ). This is mostly due to the observation that autophagy can also degrade ubiquitylated proteins.…”
mentioning
confidence: 99%
“…In the case of autophagy, the balance of active motor proteins on the surface of autophagosomes has been proposed to prevent their premature or random fusion with lysosomes (Mackeh et al., 2013). In most cells, autophagosome–lysosome fusion occurs mainly in the perinuclear region where it is facilitated through both physical proximity of the organelle and slowing of vesicular trafficking (Kimura, Noda & Yoshimori, 2008; Zaarur et al., 2014). Consequently, efficient positioning of these degradative compartments in the vicinity of the nucleus in a microtubule‐dependent manner is an essential step for the final completion of the autophagic process (Kimura et al., 2008; Monastyrska et al., 2009; Sakai, Araki & Ogawa, 1989).…”
Section: Introductionmentioning
confidence: 99%